F(x)=(2x+3)(x-2x)

Simple and best practice solution for F(x)=(2x+3)(x-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(x)=(2x+3)(x-2x) equation:



(F)=(2F+3)(F-2F)
We move all terms to the left:
(F)-((2F+3)(F-2F))=0
We add all the numbers together, and all the variables
F-((2F+3)(-1F))=0
We multiply parentheses ..
-((-2F^2-3F))+F=0
We calculate terms in parentheses: -((-2F^2-3F)), so:
(-2F^2-3F)
We get rid of parentheses
-2F^2-3F
Back to the equation:
-(-2F^2-3F)
We get rid of parentheses
2F^2+3F+F=0
We add all the numbers together, and all the variables
2F^2+4F=0
a = 2; b = 4; c = 0;
Δ = b2-4ac
Δ = 42-4·2·0
Δ = 16
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{16}=4$
$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(4)-4}{2*2}=\frac{-8}{4} =-2 $
$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(4)+4}{2*2}=\frac{0}{4} =0 $

See similar equations:

| -6(-3u+6)-5u=7(u-4)-5 | | 37=-2(22-m)+3(m-3) | | -2w-25=9(w+7) | | 3x=(12)(18) | | -7(v+2)+2v+7=6v+9 | | 43x-17-3x=19+40x-36 | | 3+15y-1=9y+57-5y | | 6x^2–3=–18x | | 5x^2=3x+23 | | 0=-4z+40 | | 4x+5/8x+5x=10 | | 2b^2=100 | | 2y2−2y−5=0 | | 4(3^-2x-4)=36 | | 5x2+9x=13x−3 | | 3y2=54 | | 16=-8v+4(v+6) | | -7=7y+7(y-3) | | 33=-6x+3(x+5) | | 15x^2+7x-20=-20 | | x2−14x+17=0 | | 2x2+4=10 | | |3x+4|=|x-13| | | -2a+40+9a=3a-6a | | 2x2=10 | | 8-2x-6-13x=5 | | 12x-97=119 | | X(x-4)-2=x2-4(x+3) | | x2−4x−3=0 | | 4(x+1)=6-x | | -5x+5=8-(5x+3) | | x²+10x-400=0 |

Equations solver categories